MEKANISME RESPON TANAMAN TERHADAP CEKAMAN KEKERINGAN - Dwi Setyo Rini; Budiarjo Budiarjo; Indra Gunawan; Radi Hidayat Agung; Rina Munazar (BERITA BIOLOGI, 2020)
Drought stress is the major abiotic stress affecting plant growth and productivity. This review emphasizes the discussion of plant response mechanisms when experiencing drought stress. The plant develops the strategies under water deficit conditions in the form of drought escape, drought avoidance, drought tolerance, or a combination of those strategies. Drought stimulates a wide variety of plant adaptation by changes in morphological, physiological, biochemical, and molecular levels. This mechanism is organized by a complex signaling network system comprising of signal perception, signal transduction pathway, and the regulation of drought-responsive genes expression.